MIDWIFERY CARE FOR PREGNANT WOMEN WITH CONDYLOMA ACUMINATA: A CASE REPORT: MIDWIFERY CARE FOR PREGNANT WOMEN WITH CONDYLOMA ACUMINATA: A CASE REPORT - Nur Anggraini, Dwi; juariah, juariah; Sasnitiari, NI Nyoman (Politeknik Kesehatan Kemenkes Bandung, 2024)
Teenage pregnancy can cause several risks to both the mother and the fetus, for the fetus there can be complications of premature birth and LBW. In the mother there can be bleeding, perineal tears and prolonged labor. In 2022, as many as 12.8 million mothers who gave birth were aged 15-19 years. In this case, the mother with a young pregnancy aged 18 years accompanied by condyloma acuminata disease has the potential for respiratory problems, vocal cord damage, and blindness in the eyes of babies infected with HPV. The methods used in compiling the Report are case reports, midwifery management approaches and SOAP documentation (Subjective, Objective, Analysis, Management). Data collection techniques use interview techniques, physical examinations, observations, documentation studies, and literature studies. Analysis in this case Mrs. D,18 years old pregnant 31 weeks with condyloma acuminata, care provided in collaboration with a SPog doctor by administering 80-90% trichloroacetic acid ointment and 0.1% gentamicin sulfate ointment therapy, education on STDs and sexuality, after two months of care condyloma acuminata resolved. The conclusion of the results of care is in accordance with the standards of pregnancy care, but there are obstacles, namely the husband who is not cooperative. The suggestion in this case is to invite the husband to undergo treatment so that the sexually transmitted disease in this couple is resolved.